Analisis Rasio Solvabilitas Untuk Menilai Kinerja Perusahaan (Studi Kasus Pada PT.Wahana Sentana Baja) - Dina Satriani; Vina Vijaya Kusuma (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
PT. Wahana Sentana Baja is a transportation company that provides transportation services for production of goods to the outside, transportation can be by land, sea, or air. The purpose of this study is for the calculation process in analyzing long-term debt accounting and as a decision-making factor to borrow maturing funds. more than one year at PT. Wahana Sentana Baja. Data collection using descriptive methods and data techniques, interviews, direct interviews, and reference books. The process of decision making and decision making is seen from the financial statements, namely the profit and loss report and the balance sheet in 2016, 2017, 2018. Then it is analyzed using the solvency ratio which is divided into three parts, the ratio of debt to equity, ratio of total debt to total assets, and ratio long-term debt or equity.